THE IMPLEMENTATION OF GUIDANCE AND COUNSELLING IN SMA (SENIOR HIGH) GOVERNMENT SCHOOL IN PALANGKARAYA - Fatchurahman, M; Bulkani, Bulkani; Supardi, Supardi (Universitas Muria Kudus, 2017)
This study was conducted based on the data from the results of interviews and documentation in several government high schools Palangkaraya that there are limitations in the mastery of information technology, lack of infrastructure, limited budget, causing the lack of application of the instrument to be used as guidelines for the implementation of guidance and counseling, including the collection of data results service becomes not routinely performed. The purpose of this study is to investigate the implementation of guidance and counseling in SMA Govenrment School Palangkaraya. This research used descriptive research, by adapting the evaluation of the two models, namely models EPIC from Hammond and Countenance Model of Stake. Data were collected through interviews, observation, and documentation. The assessment criteria is three categories; low, medium, and high. The results showed: (1) Components antecedents in the form of service characteristics as supporting the implementation of guidance and counseling in SMA Government School in Palangkaraya, categorized: Medium. (2) Components of transactions in the form of activity characteristic of services as the implementation of guidance and counseling in high schools in Palangkaraya, categorized: Low. (3) Components outcomes in the form of the results of activities in the implementation of guidance and counseling in high schools in Palangkaraya, in the form of benefits from the implementation of the guidance and counseling that marked the development of behavioral changes of students, categorized: High.